Molecular Biological Effects of Gundelia tournefortii (Kenger Herb) Extract on Oxidative Stress and Cellular Responses in Saccharomyces cerevisiae - Yılmaz, Batuhan; Fırat, Hacı; Beyaz, Seda; Nasrullah,; Aslan, Abdullah (My University, 2025)
Gundelia tournefortii (Kenger plant) is traditionally used for liver diseases, diabetes, chest pain, heart failure, stomach pain, vitiligo, diarrhea, and bronchitis. Additionally, it is known for its purgative, sedative, anti-inflammatory, antiparasitic, antiseptic, and antiemetic properties. This study investigates whether Gundelia tournefortii has a protective role against hydrogen peroxide (H2O2)-induced oxidative damage in Saccharomyces cerevisiae. In this study, four groups were established: Control group; H2O2 group (15 millimolar); G. tournefortii group (10%); G. tournefortii (10%) + H2O2 (15 millimolar) group. S. cerevisiae cultures were grown at 30°C for 1, 3, 5, and 24-hour intervals. Cell growth periods, lipid peroxidation malondialdehyde (MDA) analysis, glutathione (GSH) levels, and catalase activity (CAT) were measured using a spectrophotometer. The total protein concentration changes of S. cerevisiae cultures were determined by SDS-PAGE electrophoresis and calculated using the Bradford method. As a result, in the H2O2 group, MDA levels increased, while GSH levels and CAT activity decreased, indicating increased oxidative stress. In the G. tournefortii group, MDA levels decreased, while GSH levels and CAT activity increased, suggesting that this plant has a protective effect. The results suggest that G. tournefortii extract enhances cellular defense mechanisms by mitigating oxidative stress and promoting protein synthesis in yeast cells.
Keywords: Saccharomyces cerevisiae; Protein synthesis; Hydrogen peroxide; Oxidative damage; Gundelia tournefortii (Kenger plant)